Transcriptomic analysis of wild Cannabis sativa: insights into tissue- and stage-specific expression and secondary metabolic regulation - Jinyuan Hu; Zishi Wang; He Xu; Zhenlong Wang; Ning Li; Rui Feng; Jianyu Yin; Fangru Liu; Baishi Wang (BMC Genomics)
Abstract Cannabis sativa is a medicinally and economically significant plant known for its production of cannabinoids, terpenoids, and other secondary metabolites. This study presents a transcriptomic analysis to elucidate tissue-specific expression and regulatory mechanisms across leaves, stems, and roots. A total of 2,530 differentially expressed genes (DEGs) were identified, with key genes such as terpene synthase (TPS) and phenylalanine ammonia-lyase (PAL) exhibiting elevated expression in leaf tissues, emphasizing their roles in terpenoid and phenylpropanoid biosynthesis. Alternative splicing (AS) analysis revealed 8,729 distinct events, dominated by exon skipping, contributing to transcriptomic diversity. Long non-coding RNA (lncRNA) prediction identified 3,245 candidates, many of which displayed tissue-specific expression patterns and co-expression with metabolic genes, suggesting regulatory roles in secondary metabolism. Additionally, 12,314 SNPs and 2,786 INDELs were detected, with notable enrichment in genes associated with secondary metabolite biosynthesis, particularly in leaf tissues. These findings advance the understanding of molecular mechanisms governing secondary metabolism and genetic diversity in C. sativa, providing valuable insights for future metabolic engineering and breeding strategies to enhance cannabinoid production.